ANALISIS PENERAPAN NEW PUBLIC MANAGEMENT (NPM) SEBAGAI KERANGKA PENINGKATAN KUALITAS PELAYANAN PADA BALAI KESEHATAN/RUMAH SAKIT - Setyono, Dedi (JURNAL AKUNTANSI DAN INVESTASI, 2019)
The paradigm of New Public Management (NPM) is a system of public administration at the actual, because NPM seeks to improve the performance of the public sector as in the private sector. The application of the concept of New Public Management (NPM) has given a dramatic increase in the public sector, such as the traditional management of rigid, convoluted bureaucratic model of public sector management into a flexible, open, and more to accommodate the market. Quality improvement of service quality, NPM is able to provide optimal considerable changes in service delivery, such as transparency, simplicity, flexibility, effectiveness, efficiency, and accountability in order to obtain excellent service.